Multiple criteria decision making (MCDM) based economic analysis of solar PV system with respect to performance investigation for Indian market - Padmanathan K.; Govindarajan U.; Ramachandaramurthy V.K.; Sudar Oli Selvi T. (MDPI, 2023)
analytical hierarchy process; decision making; demand analysis; economic analysis; electricity; energy market; energy resource; life cycle; performance assessment; photovoltaic system; renewable resource; India